STX17 dynamically regulated by Fis1 induces mitophagy via hierarchical macroautophagic mechanism - Xian, Hongxu; Yang, Qiaoyun; Xiao, Lin; Shen, Han-Ming; Liou, Yih-Cherng (Nature communications, 2019)
Mitophagy is the selective autophagic targeting and removal of dysfunctional mitochondria. While PINK1/Parkin-dependent mitophagy is well-characterized, PINK1/Parkin-independent route is poorly understood. Using structure illumination microscopy (SR-SIM), we demonstrate that the SNARE protein Syntaxin 17 (STX17) initiates mitophagy upon depletion of outer mitochondrial membrane protein Fis1. With proteomics analysis, we identify the STX17-Fis1 interaction, which controls the dynamic shuffling of STX17 between ER and mitochondria. Fis1 loss results in aberrant STX17 accumulation on mitochondria, which exposes the N terminus and promotes self-oligomerization to trigger mitophagy. Mitochondrial STX17 interacts with ATG14 and recruits core autophagy proteins to form mitophagosome, followed by Rab7-dependent mitophagosome-lysosome fusion. Furthermore, Fis1 loss impairs mitochondrial respiration and potentially sensitizes cells to mitochondrial clearance, which is mediated through canonical autophagy machinery, closely linking non-selective macroautophagy to mitochondrial turnover. Our findings uncover a PINK1/Parkin-independent mitophagic mechanism in which outer mitochondrial membrane protein Fis1 regulates mitochondrial quality control. Mitophagy plays a critical role in cellular homeostasis, and PINK1/Parkin-mediated mitophagy is the most thoroughly characterized. Here, Xian et al. show that STX17 induces mitophagy via a macroautophagy pathway regulated by Fis1, by a PINK1/Parkin-independent route.